Reproductive health needs of HIV serodiscordant couples: a systematic review - Motaharinezhad, Mohadese; Yousefi, Zahra; Rostami, Sahar; Goli, Shahrbanoo; Keramat, Afsaneh (Frontiers in Public Health, 2024)
Objectives: HIV is closely linked to reproductive and sexual health. HIV Serodiscordant couples face significant social, reproductive, and sexual challenges. This systematic review aimed to identify their reproductive health needs.Methods: A comprehensive literature search was conducted across six databases: Scopus, PubMed, Web of Science, Google Scholar, Magiran, and Iranmedex. No date restrictions were applied, and only English-language articles published before February 21, 2023, were included.We also searched the grey literature and conducted forward/backward citation searches.Results: From an initial 758 articles, 18 met the inclusion criteria. Studies were qualitative (n=10) and quantitative (n=8). Key reproductive health needs included: 1) childbearing intention, 2) HIV serodiscordance and sexuality, 3) psychological and social support, 4) training and consultation services, 5) access to reliable information, and 6) focused training for healthcare providers.HIV-discordant couples face various reproductive health challenges. Implementing comprehensive guidelines for reproductive and sexual health, rehabilitation, and fertility planning is crucial to improving their quality of life and health.